Cheating During the College Years: How do Business School Students Compare? - Klein, Helen A. (Journal of business ethics, 2007)
When it comes to cheating in higher education, business school students have often been accused of being the worst offenders; if true, this may be a contributing factor in the kinds of fraud that have plagued the business community in recent years. We examined the issue of cheating in the business school by surveying 268 students in business and other professional schools on their attitudes about, and experiences with, cheating. We found that while business school students actually cheated no more or less than students in other professional schools, their attitudes on what constitutes cheating are more lax than those of other professional school students. Additionally, we found that serious cheaters across all professional schools were more likely to be younger and have a lower grade point average.